Identifying intermediates in the reductive intramolecular cyclisation of allyl 2-bromobenzyl ether by an improved electron paramagnetic resonance spectroelectrochemical electrode design combined with density functional theory calculations. (1st May 2018) - Pauwels, Danny; Vincent Ching, H.Y.; Samanipour, Mohammad; Neukermans, Sander; Hereijgers, Jonas; Van Doorslaer, Sabine; De Wael, Karolien; Breugelmans, Tom
Abstract: The electrochemical activation of C-X bonds requires very negative electrode potentials. Lowering the overpotentials and increasing the catalytic activity requires intensive electrocatalytic research. A profound understanding of the reaction mechanism and the influence of the electrocatalyst allows optimal tuning of the electrocatalyst. This can be achieved by combining electrochemical techniques with electron paramagnetic resonance (EPR) spectroscopy. Although this was introduced in the mid-twentieth century, the application of this combined approach in electrocatalytic research is underexploited. Several reasons can be listed, such as the limited availability of EPR instrumentation and electrochemical devices for such in situ experiments. In this work, a simple and inexpensive construction adapted for in situ EPR electrocatalytic research is proposed. The proof of concept is provided by studying a model reaction, namely the reductive cyclisation of allyl 2-bromobenzyl ether which has interesting industrial applications.